Elevated Urinary Connective Tissue Growth Factor in Diabetic Nephropathy Is Caused by Local Production and Tubular Dysfunction - Karin G. F. Gerritsen; Jan Willem Leeuwis; Maarten P. Koeners; Stephan J. L. Bakker; Willem van Oeveren; Jan Aten; Lise Tarnow; Peter Rossing; Jack F. M. Wetzels; Jaap A. Joles; Robbert Jan Kok; Roel Goldschmeding; et al. (Journal of Diabetes Research)
Connective tissue growth factor (CTGF; CCN2) plays a role in the development of diabetic nephropathy (DN). Urinary CTGF (uCTGF) is elevated in DN patients and has been proposed as a biomarker for disease progression, but it is unknown which pathophysiological factors contribute to elevated uCTGF. We studied renal handling of CTGF by infusion of recombinant CTGF in diabetic mice. In addition, uCTGF was measured in type 1 DN patients and compared with glomerular and tubular dysfunction and damage markers. In diabetic mice, uCTGF was increased and fractional excretion (FE) of recombinant CTGF was substantially elevated indicating reduced tubular reabsorption. FE of recombinant CTGF correlated with excretion of endogenous CTGF. CTGF mRNA was mainly localized in glomeruli and medullary tubules. Comparison of FE of endogenous and recombinant CTGF indicated that 60% of uCTGF had a direct renal source, while 40% originated from plasma CTGF. In DN patients, uCTGF was independently associated with markers of proximal and distal tubular dysfunction and damage. In conclusion, uCTGF in DN is elevated as a result of both increased local production and reduced reabsorption due to tubular dysfunction. We submit that uCTGF is a biomarker reflecting both glomerular and tubulointerstitial hallmarks of diabetic kidney disease.